Urgensi Pendekatan Multi-Interdisiplin pada Kajian Hadis di Ma’had Aly - Yuniar Indra Yahya (El Nubuwwah Jurnal Studi Hadis, 2024)
Sivagowri Sivagurunathan, Rudhad Ilaina, Suud Sarim Karimullah, and Moh Mansur Abdul Haq mention that there are many cases that cannot be explained or resolved using only one disciplinary approach, including in the study of Islam. However, on the other hand, the multi-interdisciplinary approach in hadith studies at Ma'had Aly Tebuireng does not touch even one-third of its monodisciplinary studies. Through literature review and case study research on the final projects of Ma'had Aly Tebuireng students, the researchers sought to depict the condition of the hadith study climate at Ma'had Aly Tebuireng. The first finding is that the condition of hadith studies depicted in the research pattern of Ma'had Aly Hasyim Asy'ari Tebuireng is still predominantly monodisciplinary. Monodisciplinary studies account for about 70%. This is evidenced by the theses written from 2020 to 2023. On the other hand, the multi-interdisciplinary approach in hadith studies at Ma'had Aly Tebuireng is still below 10%. However, there are several approaches that can support hadith studies, such as hermeneutics, stylistics, and ethnography. This is the second finding of this research. Therefore, approaches beyond the discipline of hadith become an urgency in the study of hadith at Ma'had Aly Hasyim.